A new approach for modeling and smoothing of scattered 3D data - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
In order to digitize the whole surface of a three-dimensional object by means of an optical range sensor, usually multiple range images are acquired from different viewpoints and merged into a single surface description. The simplest and most accurate way is to generate a polyhedral surface. The data are usually distorted by measuring errors like noise, aliasing, outliers, calibration and registration errors, etc., so that they have to be filtered. Calibration and registration errors first appear after merging of different views. As the merged data are no longer represented on a grid, conventional filters for digital signal processing are not applicable. We introduce a new approach for modeling and smoothing scattered data based on an approximation of a mesh of circular arcs. This new method enables interpolation of curved surfaces using solely the vertex position and the associated vertex normals of a polyhedral mesh. The new smoothing filter is specifically adapted to the requirements of geometric data, as it minimizes curvature variations. In contrast to linear filters, undesired surface undulations are avoided, which is an important pre-condition for NC milling and rendering.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.anewap
Keywords: Geometric modeling; Reverse engineering; Scattered data interpolation; Scattered data modeling; Smoothing of polyhedral surfaces; Surface approximation; Surface interpolation; Surface reconstruction; Surface smoothing